Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - Review Exercises - Page 234: 65


$f^{-1} (x)=5x+4$

Work Step by Step

We have $f^{-1} (x) =5x+4$ and $f(f^{-1} (x))=f(5x+4)= \dfrac{(5x+4)-4}{5}=\dfrac{5x}{5}=x$ Now, $f(f^{-1} (x))=f(\dfrac{x-4}{5})= 5(\dfrac{x-4}{5})+4=x-4+4=x$ Thus, we have $f^{-1} (x)=5x+4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.